Navigating the Purification Process: Maintaining the Integrity of Replication-Competent Enveloped Viruses - Adrian Schimek; Judy King Man Ng; Jürgen Hubbuch (Vaccines)
Replication-competent virus particles hold significant therapeutic potential in application as oncolytic viruses or cancer vaccines. Ensuring the viral integrity of these particles is crucial for their infectivity, safety, and efficacy. Enveloped virus particles, in particular, offer large gene insert capacities and customizable target specificity. However, their sensitivity to environmental factors presents challenges in bioprocessing, potentially compromising high quality standards and cost-effective production. This review provides an in-depth analysis of the purification process steps for replication-competent enveloped virus particles, emphasizing the importance of maintaining viral integrity. It evaluates bioprocessing methods from cell culture harvest to final sterile filtration, including centrifugation, chromatographic, and filtration purification techniques. Furthermore, the manuscript delves into formulation and storage strategies necessary to preserve the functional and structural integrity of virus particles, ensuring their long-term stability and therapeutic efficacy. To assess the impact of process steps on particles and determine their quality and integrity, advanced analytical methods are required. This review evaluates commonly used methods for assessing viral integrity, such as infectious titer assays, total virus particle quantification, and structural analysis. By providing a comprehensive overview of the current state of bioprocessing for replication-competent enveloped virus particles, this review aims to guide researchers and industry professionals in developing robust and efficient purification processes. The insights gained from this analysis will contribute to the advancement of virus-based therapeutics, ultimately supporting the development of safe, effective, and economically viable treatments for various diseases.